PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Wachid Hasyim; Maha Putra; Ani Wijayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Human resources (HR) are factors that play an important role in all industrial sectors and business activities. Industrial area as a place to concentrate the activities of the processing industry which is equipped with infrastructure, facilities and other supporting facilities provided and managed by the company. This study aims to determine the effect of work discipline and work environment on job satisfaction with organizational commitment as an intervening variable (a case study of company employees in the MM2100 Industrial Estate). The respondents of this study were 100 company employees in the MM2100 Industrial Estate. The type of data used is quantitative and the data processing technique uses Smart PLS. The results showed that the work discipline variable had a positive and significant effect on job satisfaction, the work environment variable had a positive and significant effect on job satisfaction, the work discipline variable had a positive and significant influence on organizational commitment and the work environment variable had a positive and significant influence on commitment. Organization and organizational commitment variables have a positive and significant effect on job satisfaction.